Real time imaging system for craniofacial reconstruction: from geomatic to medical applications - Setan, Halim; Majid, Zulkepli; Chong, Albert K.; Ahmad, Anuar (2005)

(untitled)
For medical purposes (such as craniofacial (reconstruction), human faces and skulls (i.e. soft and hard tissues) need to be modeled and measured accurately. In Malaysia, many surgeons are still using the laborious traditional contact method (for example, calipers) for measuring anthropometric landmarks on human face. Consequently, a multi-disciplinary Prioritised Research (under IRPA) is established between Universiti Teknologi Malaysia (UTM), Standards & Industrial Research Institute Malaysia (SIRIM), and Universiti Sains Malaysia (USM). The research focuses on the development of surgical planning system for craniofacial reconstruction, for both the soft and hard tissues. The craniofacial reconstruction requires the following: imaging and measurement (non-contact, precise, rapid), 3D models (digital and physical), database, and surgical planner. This paper discusses the research works undertaken by UTM on the development of the imaging system (close range, non-contact, and real time) and information system (i.e. database) for craniofacial. The real time imaging system combines the laser scanning and photogrammetric techniques for acquiring high-resolution 3D models of craniofacial soft tissue. The information system integrates various inputs (soft tissue from laser scan and photogrammetry, hard tissue from CT-scan, measurement, patient’s information, etc) for managing and visualizing the craniofacial data. Some actual results are shown to highlight the developed approach.